Pemberdayaan Masyarakat Desa Talang Arah Berbasis Teknologi Mandiri Sesuai Dengan Peraturan Pemerintah Daerah - Selviani, Diah; Wahyudi , Jusuf; Elfianty , Lena; Maryani , Desy; Rachayu , Imma; Martianti; Lorita, Evi; Alani , Gina Dwi (Jurnal Kewirausahaan dan Bisnis, 2022)
This study aims to analyze and implement community empowerment in Talang Arah Village based on local government regulations that lead to independent use of technology. Community empowerment is a process that aims to improve the quality of life of the community by providing the necessary knowledge, skills and resources so that they can actively participate in local development. Talang Arah Village is an area located in a rural area that still faces various development challenges, including limited access to technology. Local government regulations support community empowerment and encourage the use of technology to improve quality of life and development in the region. This research will use a qualitative approach with a case study method in Talang Arah Village. Data will be collected through interviews with relevant stakeholders, direct observation, and analysis of local government regulatory documents related to community empowerment and technology. The results of this study are expected to provide a better understanding of community needs and the potential for developing technologies that are relevant to local conditions in Talang Arah Village. In addition, this research will also identify obstacles and opportunities in implementing independent technology-based community empowerment in accordance with government regulations.